Swept‐source optical coherence tomography objective composite activity score for uveitis. Issue 7 (9th January 2021) - Llorenç, Victor; Serrano, Alba R.; Mesquida, Marina; Lin, Phoebe; Esquinas, Cristina; Sainz‐de‐la‐Maza, Maite; Metea, Christina; Bosch, Anna; Calvo, Maria; Balter, Ariel; Nakamura, Yukiko; Molins, Blanca; et al.
Abstract: Purpose: To develop an objective intraocular inflammation composite score. Methods: Cross‐sectional study. Non‐invasive image acquisition and processing were conducted from April 2017 to April 2019. Inflammation‐grade stratified eyes from patients with active, inactive uveitis and healthy controls were recruited. After clinical assessment, four anterior and posterior segment image acquisition protocols per eye, using swept‐source optical coherence tomography (SS‐OCT), were performed at inclusion. Eight imaging biomarkers in three domains: anterior, intermediate and posterior were studied. They were ranked and selected by discriminatory power and correlation with clinical scores. A final SS‐OCT‐derived composite uveitis activity score (SS‐UAS) was developed through multiple linear regression. Results: We studied 224 eyes with uveitis (165 active and 59 inactive) from 165 patients (mean age 46.6 SD 15.5 years; 55.3% women) and 38 eyes from 19 healthy controls (mean age 43.6 SD 17.1; 47% women). The selected SS‐OCT‐derived biomarkers to build the final score were anterior chamber hyper‐reflective dots (anterior), high‐definition relative vitreous intensity (intermediate) and the averaged thickened retinal index (posterior). Swept‐source (SS)‐UAS was highly discriminant between active and inactive, and between active and healthy eyes (means 2.06 SD 1.86, 0.93 SD 0.44, and 0.96 SD 0.38, respectively, both p ‐, Mann–Whitney U ). Construct validity (Cronbach's alpha = 0.7), internal consistency, criterion validity and reliability (concordance correlation coefficient intra‐rater = 0.99, 95% CI: 0.98–0.99; inter‐rater = 0.98, 95% CI: 0.96–0.99) were favourable. Conclusions: Global intraocular inflammation can potentially be staged and scored objectively, continuously, consistently and in a valid manner through the combined processing of SS‐OCT scans.